2018
DOI: 10.1080/0284186x.2018.1477256
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia associates with poor outcome in metastatic renal cell carcinoma patients treated with everolimus: prognostic impact

Abstract: Hyponatremia associates with poor outcome in mRCC patients treated with everolimus. On-treatment normalization of hyponatremia to normal sodium values associates with favorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Recently, a study performed at two teaching hospitals in Italy and one teaching hospital in England demonstrated that serum [Na + ] normalization during first-line therapy is an independent prognostic factor for OS and PFS in patients with non-small cell lung cancer [37] . Similarly, normalization of serum [Na + ] was associated with a better prognosis in patients with metastatic RCC treated with everolimus [38] . These findings are in agreement with the results of a meta-analysis that analyzed articles reporting the outcome of patients with different diseases in which hyponatremia had been corrected.…”
Section: Why Is Hyponatremia Associated With a Worse Outcome In Cancementioning
confidence: 89%
“…Recently, a study performed at two teaching hospitals in Italy and one teaching hospital in England demonstrated that serum [Na + ] normalization during first-line therapy is an independent prognostic factor for OS and PFS in patients with non-small cell lung cancer [37] . Similarly, normalization of serum [Na + ] was associated with a better prognosis in patients with metastatic RCC treated with everolimus [38] . These findings are in agreement with the results of a meta-analysis that analyzed articles reporting the outcome of patients with different diseases in which hyponatremia had been corrected.…”
Section: Why Is Hyponatremia Associated With a Worse Outcome In Cancementioning
confidence: 89%
“…Low sodium is associated with poor disease-free and overall survival after nephrectomy. It could act as a new independent prognostic and predictive factor in patients with mRCC 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier endeavors have shown the negative prognostic aspect of hyponatremia in a variety of cancers [19,20]. Yoon et al have also demonstrated a relation between hyponatremia and shorter survival time in terminally ill cancer patients [21].…”
Section: Discussionmentioning
confidence: 99%